Evaluating the consistency of the 1982-1999 NDVI trends in the Iberian Peninsula across four time-series derived from the AVHRR sensor : LTDR, GIMMS, FASIR, and PAL-II - Alcaraz Segura, Domingo (2010)
Fil: Alcaraz Segura, Domingo. Universidad de Almería. Centro Andaluz para la Evaluación y Seguimiento del Cambio Global–CAESCG. Departamento de Biología Vegetal y Ecología. Almería, Spain.